2021
DOI: 10.1186/s40580-021-00256-9
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic hydrogen evolution from biomass conversion

Abstract: Biomass has incredible potential as an alternative to fossil fuels for energy production that is sustainable for the future of humanity. Hydrogen evolution from photocatalytic biomass conversion not only produces valuable carbon-free energy in the form of molecular hydrogen but also provides an avenue of production for industrially relevant biomass products. This photocatalytic conversion can be realized with efficient, sustainable reaction materials (biomass) and inexhaustible sunlight as the only energy inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 118 publications
0
53
0
Order By: Relevance
“…Already, typically used for the removal of organic contaminants from wastewater, the heterogeneous photocatalysis offers the opportunity to achieve molecular hydrogen production under the irradiation, by reforming of organic molecules in liquid phase. Indeed, in literature, it is reported that biomass photoreforming is a promising method for the molecular hydrogen production, not only because the method relies on predictably infinite solar energy inputs, but also it is based on a renewable biomass substrate and could use by-products of industrial biomass processes existing, e.g., ethanol from sugar fermentation [7,8]. The photoreforming process improves the well-known process of photocatalytic water-splitting [9] since the organic components acts as a hole scavengers, overcoming the main drawbacks of the water-splitting as unfavorable thermodynamics and rapid recombination of the O 2 and H 2 produced [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Already, typically used for the removal of organic contaminants from wastewater, the heterogeneous photocatalysis offers the opportunity to achieve molecular hydrogen production under the irradiation, by reforming of organic molecules in liquid phase. Indeed, in literature, it is reported that biomass photoreforming is a promising method for the molecular hydrogen production, not only because the method relies on predictably infinite solar energy inputs, but also it is based on a renewable biomass substrate and could use by-products of industrial biomass processes existing, e.g., ethanol from sugar fermentation [7,8]. The photoreforming process improves the well-known process of photocatalytic water-splitting [9] since the organic components acts as a hole scavengers, overcoming the main drawbacks of the water-splitting as unfavorable thermodynamics and rapid recombination of the O 2 and H 2 produced [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose behaves like a sacrificial agent through the depolymerization of cellulose into glucose products by oxidizing species and combines with the photo-generated oxidant species suppressing charge carrier recombination. In general, glucose represents one of the most efficient sacrificial substances for the photocatalytic production of hydrogen [8]. The photocatalytic production of hydrogen was studied for several years and there are many catalysts used for this purpose, such as TiO 2 based photocatalysts [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported the electrochemical surface modification of electrode materials including glassy carbon, carbon nanotube, and indium tin oxide (ITO) via electro‐oxidative coupling of amine‐terminated dendrimers 12–14 . The electrochemical modification of electrode surfaces with dendrimers has provided an effective and unique means for surface decoration of electrodes with catalytic nanoparticles because the dendrimers are capable of encapsulating various types of catalytic nanoparticles inside their internal cavity 15–19 . In order to further expand the scope of dendrimers for application in the electrochemical surface modification, our attention has been directed to hydroxyl‐terminated dendrimers as well.…”
Section: Figurementioning
confidence: 99%